Prolonged Pulsed Radiofrequency Treatment in Resistant Trigeminal Neuralgia: A Case Report - Seyyed Masoud Hashemi; Faranak Behnaz; Sina Hassannasab; Sogol Asgari (Archives of Anesthesia and Critical Care)
Trigeminal neuralgia (TN) is one of the most severe painful conditions known to man. Contradictory results regarding the effectiveness of pulsed radiofrequency (PRF) treatment of the trigeminal ganglion have been published in the literature. In the past few years, reports in support of prolonged (extended duration) radiofrequency treatment of the trigeminal ganglion have been emerging. Unlike most other interventional procedures that include nerve or ganglion destruction and its resultant potential complications, PRF treatment is believed to be much safer. Working toward the establishment of effective PRF protocols proves highly valuable in the management of TNs refractory to medical treatment. This article showcases the successful control of two cases of refractory trigeminal neuralgia (TN) through extended duration pulsed radiofrequency treatment. Recent studies, however, suggest prolonged PRF ablation may provide a more durable solution. PRF offers a potentially safer alternative to traditional interventions by minimizing nerve destruction.